Negative myoclonus secondary to paroxetine intake. (24th April 2018) - Correia, Pedro; Ribeiro, Joana Afonso; Bento, Conceição; Sales, Francisco
Abstract : Outside the context of overdose and serotonin syndrome, seizures and myoclonic movements attributed to selective serotonin reuptake inhibitors (SSRIs) are rare and poorly documented. We present a 77-year-old man, with no history of epilepsy, presenting in the emergency department with whole body jerks since that morning. Two days earlier, due to a prescription mistake, he was started on paroxetine 20 mg instead of his usual fluoxetine 20 mg. The patient's electroencephalogram (EEG), performed in the emergency department, revealed a bilateral synchronous parieto-occipital fast spike activity pattern, which correlated consistently with negative myoclonus. Two days after stopping paroxetine, the patient presented no seizures and no abnormalities in the EEG. We present an EEG documented case of drug-induced seizures, with a bilateral parieto-occipital pattern, secondary to paroxetine intake. A hyperexcitability of the primary somatosensory cortex inhibiting primary motor cortex output could explain the electroclinical correlation.